Comparative evaluation of satranidazole and ornidazole effectiveness in the treatment of chronic periodontal diseases along with mechanical debridement - Awasthi, Bharat Bhushan; Singh, Saurabh (International Journal of Research in Medical Sciences, 2018)
Background: Periodontitis is a common chronic inflammatory dental disease, which occurs due to the existence of pathogenic microorganisms within the gingival plaque and lead to the formation of periodontal pocket. This study was aimed to evaluate the effectiveness of satranidazole and ornidazole in the treatment of chronic periodontal diseases along with mechanical debridement. Methods: Forty subjects were randomly selected to access the effectiveness of selected drugs on the basis of clinical and microbiological investigations over a period of 14 days. Six Ramfjord teeth (i.e. 16, 21, 24, 36, 41 and 44) were examined for investigating clinical parameters such as gingival inflammation, pocket depth and bleeding on probing. Microbiological investigations were carried out to examine the presence of gram positive (cocci and bacilli), gram negative (cocci and bacilli) and spirochaetes. Results: A substantial progress was recorded in treating gingival inflammation, pocket depth and bleeding on probing. The results of microbiological investigations suggest that the satranidazole and ornidazole were equally effective when used alone and with scaling and root planning in reducing microbial infections. The results indicated a significant (p <0.0001) effect of model drugs on clinical and microbiological parameters in different study subjects at baseline (pre-treatment), and 7 days and 14 days post treatment. Conclusions: The results concluded that ornidazole is better than satranidazole in treating periodontal diseases.